Association of problematic usage of the internet with burnout, depression, insomnia and quality of life among Hungarian recreational esports players: a cross sectional study - Feher, Andrea; Fejes, Eva; Feher, Gergely; Horvath, Lilla; Tibold, Antal (Frontiers in Public Health, 2025)
BackgroundWhile recreational esports are often considered a harmless hobby, problematic internet use (PUI) may be an overlooked risk factor for poor mental health outcomes.ObjectiveThis study aimed to investigate the associations between PUI and depression, burnout, insomnia, and quality of life in adult Hungarian recreational esports players.MethodsA total of 2,313 participants completed validated questionnaires, including the Problematic Internet Use Questionnaire (PIUQ), the Maslach Burnout Inventory (MBI), the 9-item short form of the Beck Depression Inventory (BDI-SF), the Athens Insomnia Scale, and the EQ-5D quality of life instrument. Statistical analyses included Student’s t-test, chi-square test (χ2), Pearson’s correlation, and multivariate logistic regression. Model fit was evaluated using the Hosmer-Lemeshow test, Nagelkerke R2, and area under the receiver operating characteristic curve (AUC-ROC).ResultsExcessive internet use, as indicated by the PIUQ, was detected in 19.9% of respondents. PUI was significantly associated with emotional exhaustion (OR = 1.10, 95% CI: 1.08–1.12, p < 0.001), moderate to severe depression (OR = 3.25, 95% CI: 2.55–4.14, p < 0.001), severe insomnia (OR = 2.75, 95% CI: 1.85–4.08, p < 0.001), and reduced self-sufficiency as measured by the EQ-5D (OR = 1.85, 95% CI: 1.45–2.36, p < 0.001). The final model demonstrated good fit (Hosmer-Lemeshow p = 0.21), strong explanatory power (Nagelkerke R2 = 0.42), and excellent discrimination (AUC = 0.86).ConclusionProblematic internet use is significantly associated with multiple adverse mental health outcomes among recreational gamers. These findings suggest the need for increased awareness and preventive strategies targeting PUI in adult populations engaged in digital entertainment.